Charismatic Leadership, Joyful Learning, and Student Engagement in Maritime Vocational Education: The Moderating Role of Gender-Based Experiences - Nazarwin Nazarwin; Yunia Wardi; Rino Rino; Abror Abror; Syafni Yelvi Siska (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2026)
This study investigates the effects of charismatic leadership and a joyful-learning approach on student engagement in a vocational maritime context at Politeknik Pelayaran Sumatera Barat. A census sampling strategy was employed (N = 368; 305 male, 63 female). Data were collected using a 20-item Likert-scale instrument (pilot-tested with n = 60) and analyzed via partial least squares structural equation modelling (PLS-SEM). The structural model explained a substantial proportion of variance in student engagement (R² = 0.908). Joyful learning demonstrated a large, positive, and statistically significant effect on engagement (p < 0.001). In contrast, charismatic leadership exhibited a small and non-significant effect (p = 0.127). Gender-based experiences showed a small but statistically significant direct effect on engagement (p < 0.001), yet did not significantly moderate the relationships between the predictors and engagement. These findings underscore the primacy of pedagogical design over instructor leadership style in fostering student engagement in vocational education. Specifically, practice-oriented and affectively engaging instructional strategies appear more influential than charismatic leadership behaviors. Practically, educators should prioritize the integration of joyful, experiential learning approaches. Future research should adopt more balanced samples, employ multi-group or experimental designs, and utilize more granular measures of gender-based experience to better elucidate subgroup differences and underlying causal mechanisms.